IDENTIFICATION AND MINIMIZATION OF WASTE TO IMPROVE THE PRODUCTION PROCESS OF JAMU CAPE COFFEE USING A LEAN MANUFACTURING APPROACH - Rakhmawati,,; Matnur Setyo Budi,; Dian Farida Asfan, (International Journal of Innovations in Engineering Research and Technology, 2023)
The herbal chili plant (Piper retrofractum Vahl) is a type of plant that is widely used in Indonesia and grows on vines. This plant contains many natural ingredients that are beneficial for health. a type of medicinal plant that is widely used in Indonesia which grows climbing. In Indonesia, herbal chilies are often found in Java, Sumatra, Bali, Nusa Tenggara and Kalimantan. CV. Nurul Jannah is an agroindustry which processes garden products such as jabe jamu, moringa, coffee, etc. On CV. Nurul Jannah, the herbal chili coffee production process is a product that many people are interested in. In making herbal chili coffee, CV. Nurul Jannah gets the raw materials for coffee from Jember Regency, while the herbal chilies are obtained from the area around the company, and other supporting materials are obtained from Sumenep. For processing itself, use manual methods. That's why it reaps a lot of waste. activities that do not add value or contribute to the product which can cause customer satisfaction and decreased production. To reduce waste, use the lean manufacturing concept. Lean manufacturing itself is a systematic approach to identifying and eliminating waste through a series of improvement activities. Lean manufacturing itself is a method for minimizing waste in the production process. In PCE production before repairs it was 30.1%, this occurred due to waste such as waiting time, defects, excess processing, motion and transportation. After the process was carried out the improvement was 36.7%. This value increased significantly.